Análisis y relación entre los valores cert de la cultura BPM y los valores institucionales de empresas destacadas en Colombia (2019)
It is essential for the organization that in the planning process there is a participation and inclusion of all employees, where their experience and knowledge is taken into account, to generate a greater commitment on their part with the institutional vision, mission and values, as well as a conviction and appropriation of agreements, to finally obtain compliance with what is established in the short, medium and long term. It is inevitable, the influence that individuals bring as people, in their actions and decisions developed in the company, that is, ethics and personal values ​​influence the organization, positively or not affecting the experience of the organizational culture that arises. However, this study aims to clarify how, based on traditional organizational values, a transition is achieved and improved to reach the desired values ​​within a BPM culture. This article studies the way in which the organizational values ​​of Colombian recognized companies and the CERT values ​​proposed by a BPM culture are related, in order to know whether or not a transition can be made from the typical organizational culture to the process culture or BPM and propose a way forward to achieve it.